\(\displaystyle{H}{\left({s}\right)}={\frac{{{s}-{5}}}{{{\left({s}-{3}\right)}{\left({s}-{1}\right)}}}}\) The inverse Laplace transform of H(s)

jisu61hbke 2022-03-31 Answered
H(s)=s5(s3)(s1)
The inverse Laplace transform of H(s) is equal to
fg
You can still ask an expert for help

Want to know more about Laplace transform?

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

microsgopx6z7
Answered 2022-04-01 Author has 14 answers
Note that we can write
F(s)=s5s3=12s3
Then, f(t)=δ(t)2e3tu(t) and
h(t)=0tett(δ(t)2e3t)dt
=etet(e2t1)
=2ete3t
Note that partial fraction expansion makes things easier. We simply write
H(s)=2s11s3
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2021-09-07
Laplace transform
u(t) is the unit step function
Find the Laplace transform of the following continuous-time signal.
x(t)=4te5tu(t)
asked 2021-05-29

The integrating factor method, which was an effective method for solving first-order differential equations, is not a viable approach for solving second-order equstions. To see what happens, even for the simplest equation, consider the differential equation y+3y+2y=f(t). Lagrange sought a function μ(t)μ(t) such that if one multiplied the left-hand side of y+3y+2y=f(t) bu μ(t)μ(t), one would get μ(t)[y+y+y]=dddt[μ(t)y+g(t)y] where g(t)g(t) is to be determined. In this way, the given differential equation would be converted to ddt[μ(t)y+g(t)y]=μ(t)f(t), which could be integrated, giving the first-order equation μ(t)y+g(t)y=μ(t)f(t)dt+c which could be solved by first-order methods. (a) Differentate the right-hand side of μ(t)[y+y+y]=dddt[μ(t)y+g(t)y] and set the coefficients of y,y' and y'' equal to each other to find g(t). (b) Show that the integrating factor μ(t)μ(t) satisfies the second-order homogeneous equation μμ+μ=0 called the adjoint equation of y+3y+2y=f(t). In other words, althought it is possible to find an "integrating factor" for second-order differential equations, to find it one must solve a new second-order equation for the integrating factor μ, which might be every bit as hard as the original equation. (c) Show that the adjoint equation of the general second-order linear equation y+p(t)y+q(t)y=f(t) is the homogeneous equation μp(t)μ+[q(t)p(t)]μ=0.

asked 2021-12-11
Find the Laplace transform of
f(t)=10e200tu(t)
Would it be correct to take out the 10 because it is a constant, find the Laplace transform of e200t and then multiply it by the Laplace transform of u(t) to obtain a final answer of
10(1s+200)(1s)
The u(t) is what is really confusing me in this problem.
asked 2021-02-20
Find the inverse Laplace transform of (any two)
i) (s2+3)s(s2+9)
ii) log((s+1)(s1))
asked 2021-12-31
Solve the following differential equations.
y4y=0
asked 2022-04-14
Laplace transform of f(t)=tetsin(2t)
asked 2021-02-26
Make and solve the given equation x dx + y dy=a2x dy  y dxx2 + y2

New questions